2012
DOI: 10.1080/17470218.2012.711335
|View full text |Cite|
|
Sign up to set email alerts
|

A peculiar prevalence of p values just below .05

Abstract: In null hypothesis significance testing (NHST), p values are judged relative to an arbitrary threshold for significance (.05). The present work examined whether that standard influences the distribution of p values reported in the psychology literature. We examined a large subset of papers from three highly regarded journals. Distributions of p were found to be similar across the different journals. Moreover, p values were much more common immediately below .05 than would be expected based on the number of p v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
245
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(271 citation statements)
references
References 30 publications
12
245
2
3
Order By: Relevance
“…However, the presence of an arbitrary threshold may contribute to the number of positive findings reported in the literature. Masicampo and Lalande (2012) surveyed the distributions of p-values in three prominent psychological journals and found that p-values were conspicuously more common than expected just below α.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of an arbitrary threshold may contribute to the number of positive findings reported in the literature. Masicampo and Lalande (2012) surveyed the distributions of p-values in three prominent psychological journals and found that p-values were conspicuously more common than expected just below α.…”
Section: Introductionmentioning
confidence: 99%
“…Using what are called caliper tests, more comprehensive analyses of p-values in sociology have shown a striking difference in the percentages of z-scores that imply p-values slightly below 0.05 compared to those slightly above 0.05 Auspurg and Hinz 2011). Such findings are not at all unique to sociology (e.g., Gerber and Malhotra [2008b] for political science; Masicampo and Lalande [2012] for psychology), and they provide definitive indication of a specifically p-oriented publication bias in the scientific literature of many fields (Dwan et al 2008).…”
Section: The Cost Of Concisionmentioning
confidence: 82%
“…In studies with true nonsignificant results, the distribution of p-value will have a left skew. 1,5 The two-tailed sign test is used in combination with the P-curve analysis to identify possible P-hacking. It consists of two p-value ranges, 0<p < 0.025 and 0.025 < p < 0.05.…”
Section: Interpreting the P-curvementioning
confidence: 99%